The Use of The Maestro Music Application in Creative Music Learning For Grade XI Science Students - Samosir, Rully Yohanes; Widiastuti, Uyuni (Jurnal Seni Musik, 2024)
This research aims to: (1) describe the process of using Maestro Music application in learning creative music in class XI MIA 3 SMA Negeri 2 Padangsidimpuan; (2) evaluate the results of using Maestro Music application in learning creative music in class XI MIA 3 SMA Negeri 2 Padangsidimpuan;and (3) describe the benefits of using Maestro Music application in learning creative music. The sample for this study consisted of 8 individuals, namely 1 art teacher of SMA Negeri 2 Padangsidimpuan and 7 students from grade XI MIA 3 SMA Negeri 2 Padangsidimpuan. The research method used was qualitative with descriptive approach. Data collection techniques included observation, interviews, and documentation. The research results show: (1) The process of using the Maestro Music application in learning creative music in class XI MIA 3 involves several stages, including downloading the application, providing instructional videos about the Maestro Music application via video links, offering practice exercises such as transcribing song scores into the Maestro Music application; (2) The benefits of using the Maestro Music application in learning creative music.